Geology, Petrography and Structural analysis of Jada area, Northeastern Nigeria - Ahmed, H. A.; Halilu, M.; Salisu, I. A.; Vandi, D. K. (IJRDO-Journal of Applied Science, 2017)
The study area, forms part of the Hawal massive regarded as an extension of Bamenda massive that forms part of the Cameroun volcanic line in the Northeastern part of Nigeria (Ekwueme 1993). Eighteen samples collected in the study area were used for petrographic analyses in addition to the geological field mapping and structural analysis. The hand specimen descriptions and results of microscopic studies of the collected samples in the area revealed that quartz, feldspar and biotite are the predominant minerals in the rocks exposed, which are mainly granites, gneisses, diorites. Field relations and petrographic analysis suggest the occurrence of alkaline rocks in the study area and series of thermo-tectonic activities that resulted into numerous structural features and emplacement of different rock units that might have significant resource potentials.